Market Shares and Profitability of Universal Banks in Ghana - Amo, O. (University of Ghana, 2015)
The increasing competition among banks in Ghana is largely explained by the liberalisation and implementation of the various financial sector reforms recommended by the International Monetary Fund (IMF) and the World Bank. In today’s competitive world, one of the challenges facing many managers in the banking sector is how to increase business market shares and profits concurrently. Although the correlation between market shares and profitability has been sustained over the years, it remains a generalisation which has been over-extended without its attributes acknowledged. The question frequently asked is whether higher market share leads to higher profits? The study therefore seeks to analyse the factors that influence bank’s market share and also to examine the relationship between market share and profitability of universal banks in Ghana. A panel data of 15 universal banks in Ghana are analysed over a period of 2004 to 2013 using the Generalised Method of Moment (GMM) and random effect regression models. Results from the study indicate that, bank size, operating efficiency, bank age, number of branches, ownership structure, Gross Domestic Product and inflation significantly determine market share. The study also reveals that, there is no significant relationship between market share and profitability. The study recommends that, banks employ more technologies to facilitate their service delivery and ensure the efficient management of bank operations to help alleviate the high operational cost that erodes bank profits. Also, management need to understand the context of their environment before adoption of market share strategy.
Thesis (MPhil) - University of Ghana, 2015